Determining propulsive force in front crawl swimming: A comparison of two methods - Berger, M. A.; Hollander, A. P.; de Groot, G. (Journal of Sports Sciences, 1999)
To evaluate the propulsive forces in front crawl arm swimming, derived from a three-dimensional kinematic analysis, these values were compared with mean drag forces. The propulsive forces during front crawl swimming using the arms only were calculated using three-dimensional kinematic analysis combined with lift and drag coefficients obtained in fluid laboratories. Since, for any constant swimming speed, the mean propulsive force should be equal to the mean drag force acting on the body of the swimmer, mean values of the calculated propulsive forces were compared with the mean drag forces obtained from measurements on a Measuring Active Drag (MAD) system. The two methods yielded comparable results, the mean difference between them being only 5% (2N). We conclude that propulsive forces obtained from three-dimensional kinematic analysis provide realistic values. The calculation of the propulsive force appears to be rather sensitive to the point on the hand at which the velocity is estimated and less sensitive to the orientation of the hand.